Interpretation of the Effects of Job Satisfaction Mediation on the Effect of Principal Supervision and Compensation on Teacher Performance - Sherly, Sherly; Lie, Darwin; Candra, Vivi; Siallagan, Dolly Miduk; Sudirman, Acai (Universitas Negeri Makassar, 2021)
This research aims to determine the role of job satisfaction as a mediator of the relationship between principal supervision and compensation for teacher performance. The research design used a quantitative approach to causality. To obtain research data using documentation instruments and distributing questionnaires online. The sample used in the study was 215 respondents. The basis for determining the sample is oriented towards a non-probability sampling approach using a purposive sampling formula. To test the mediating effect of satisfaction and the relationship between principal supervision and compensation on teacher performance, a structural equation modeling (SEM) approach is used using partial least squares. Under the research results, It was found that the fact that principal supervision had a significant effect on job satisfaction and teacher performance. Then compensation also has a significant effect on job satisfaction and teacher performance. The findings of the mediation effect state that job satisfaction successfully mediates the relationship between principal supervision and compensation for teacher performance